Risk groups of laryngeal cancer treated with chemoradiation according to nomogram scores – A pooled analysis of RTOG 0129 and 0522. (May 2021) - Awan, Musaddiq J.; Gittleman, Haley; Barnholtz-Sloan, Jill; Machtay, Mitchell; Nguyen-Tan, Phuc Felix; Rosenthal, David I.; Schultz, Christopher; Huth, Bradley J.; Thorstad, Wade L; Frank, Steven J.; Kim, Harold; Foote, Robert L.; et al.
Highlights: Patient selection for laryngeal preservation remains a significant clinical problem. We developed nomograms for larynx cancer outcomes using cooperative group trial data. These nomogram scores can stratify patients by both mortality and risk of recurrence. Abstract: Objectives: To develop nomograms predicting overall survival (OS), freedom from locoregional recurrence (FFLR), and freedom from distant metastasis (FFDM) for patients receiving chemoradiation for laryngeal squamous cell carcinoma (LSCC). Material and methods: Clinical and treatment data for patients with LSCC enrolled on NRG Oncology/RTOG 0129 and 0522 were extracted from the RTOG database. The dataset was partitioned into 70% training and 30% independent validation datasets. Significant predictors of OS, FFLR, and FFDM were obtained using univariate analysis on the training dataset. Nomograms were built using multivariate analysis with four a priori variables (age, gender, T-stage, and N-stage) and significant predictors from the univariate analyses. These nomograms were internally and externally validated using c-statistics (c) on the training and validation datasets, respectively. Results: The OS nomogram included age, gender, T stage, N stage, and number of cisplatin cycles. The FFLR nomogram included age, gender, T-stage, N-stage, and time-equivalent biologically effective dose. The FFDM nomogram included age, gender, N-stage, and number of cisplatin cycles. Internal validation of the OS nomogram, FFLR nomogram, and FFDM nomogram yielded c = 0.66, c = 0.66 and c = 0.73, respectively. External validation of these nomograms yielded c = 0.59, c = 0.70, and c = 0.73, respectively. Using nomogram score cutoffs, three risk groups were separated for each outcome. Conclusions: We have developed and validated easy-to-use nomograms for LSCC outcomes using prospective cooperative group trial data.